Organizational Climate and Its Relationship to Job Performance Among a Sample of Al-Birr and Social Service Association staff. (Damascus University Journal of arts and humanities sciences, 2025)
This research aims at determining the level of organizational climate among Al-Birr and Social Service Association in Daraa city and finding variances on the scale of organizational climate based on variables (job title، nature of work, years of experience). Furthermore, it seeks to determine the level of job performance of a sample members and identify differences on the job performance scale based on variables (job title, nature of work, years of experience), as well as identify statistical differences regarding the relationship between   organizational climate and job performance Among a Sample of Al-Birr and Social Service Association staff in Daraa city.The descriptive analytical technique was used in the research, which helps explain and analyze phenomena.To achieve the objectives of the research, a measure of organizational climate was designed that included four dimensions (Management style, techniqueand  technology, work incentives, work environment) and a measure of job performance that included three dimensions (quality of work performed, volume of work performed, knowledge of job requirements), and they were applied to 100 employees working for Al-Birr and Social Service Association.The results indicated that the organizational climate is moderate, and the sample's participants showed a moderate level of job performance. The relationship between organizational climate and professional performance is significant and favorable. According to the job title variable, there are statistically significant differences on both scales in favor of the managers. According to the years of work variable, there aren’t  statistically significant variations on both scales. According to the variable of the type of work, there are statistically significant differences on both scales in favor of the category that works in  the office.
Keywords: Organizational Climate; Job Performance; Open Climate